2020
DOI: 10.1017/s1759078720000239
|View full text |Cite
|
Sign up to set email alerts
|

Design of a compact high gain printed octagonal array of spiral-based fractal antennas for DBS application

Abstract: This paper presents a compact octagonal array of microstrip patch antennas for direct broadcast satellite (DBS) (12.2–12.7 GHz) services. The proposed single element of this array is a new fractal antenna, having considerably high gain and can heavily suppress cross polarization along the main beam direction. The single element is derived from a 2D spiral geometry. The corporate feed network of the array is designed in such a manner to make the structure very compact. The fabricated single element resonates at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 36 publications
(63 reference statements)
0
6
0
Order By: Relevance
“…One major difference in enabling technology for 4G and 5G communication is using millimeter wave (mmWave) frequencies, aiming for wider bandwidth and better spectral efficiency [4]. However, moving away from the current mobile service frequencies (<4 GHz), up closer to the mm-wave bands, introduces new features that require cautious consideration [5][6][7]. For wireless applications, Kaushik Mandal and Partha Pritam Sarkar [8] developed a wideband high-gain antenna in the shape of a U, with modified ground structures.…”
Section: Introductionmentioning
confidence: 99%
“…One major difference in enabling technology for 4G and 5G communication is using millimeter wave (mmWave) frequencies, aiming for wider bandwidth and better spectral efficiency [4]. However, moving away from the current mobile service frequencies (<4 GHz), up closer to the mm-wave bands, introduces new features that require cautious consideration [5][6][7]. For wireless applications, Kaushik Mandal and Partha Pritam Sarkar [8] developed a wideband high-gain antenna in the shape of a U, with modified ground structures.…”
Section: Introductionmentioning
confidence: 99%
“…Panda et al 26 proposed a bow‐tie‐shaped wideband antenna for wireless applications. A concave L‐shaped flap‐oriented coplanar antenna for multi‐band applications is proposed by Bag et al 27 Substrate integrated waveguide (SIW) based hexagonal‐shaped antenna is reported by Liu et al 28 A high‐gain spiral‐shaped printed antenna has been proposed for direct broadcast satellite applications by Kola et al 29 An open‐ended SIW‐based U‐shaped antenna for Ku‐band applications is proposed by Ameen et al 30 The wireless application based high‐gain printed antenna is reported by Kola et al 31 Wang et al 32 claimed that the developed U‐slot inside the radiator helps to enhance the parametric results in terms of directivity and return‐loss bandwidth. A four‐element antenna array could improve parametric results as reported in several literature 33–44 …”
Section: Introductionmentioning
confidence: 99%
“…Antennas laminated using printed circuit board technology is widely used in various fields of modern communication systems. [1][2][3][4][5][6][7][8] Due to their robustness, light weight, easy of fabrication and low-profile, they are attractive for the applications such as radar, 1,2 electronic support measurements, 1,2 mobile communication, 1,2 vehicular communication, [3][4][5][6] satellite broadcasting 7,8 etc. The primary use of the spectrum under X-band communication finds application mainly in military radars and ship based communication services.…”
Section: Introductionmentioning
confidence: 99%